Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858305
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Benefit Study of Text Entry Suggestion Interaction

Abstract: Mobile keyboards often present error corrections and word completions (suggestions) as candidates for anticipated user input. However, these suggestions are not cognitively free: they require users to attend, evaluate, and act upon them. To understand this trade-off between suggestion savings and interaction costs, we conducted a text transcription experiment that controlled interface assertiveness: the tendency for an interface to present itself. Suggestions were either always present (extraverted), never pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 30 publications
5
52
0
Order By: Relevance
“…They also liked that text entry felt faster and easier in the Phrase condition, but some commented about spending a lot of time reading phrase suggestions (though there was no significant difference in ratings on "I felt like I spent a lot of time reading the suggestions": Phrase mean 3.0, Word mean 2.6, F(1,15)=1.5, n.s.). Participants commented that both Word and Phrase suggestions were often distracting, confirming the findings of a prior study [28].…”
Section: Subjective Measuressupporting
confidence: 79%
See 2 more Smart Citations
“…They also liked that text entry felt faster and easier in the Phrase condition, but some commented about spending a lot of time reading phrase suggestions (though there was no significant difference in ratings on "I felt like I spent a lot of time reading the suggestions": Phrase mean 3.0, Word mean 2.6, F(1,15)=1.5, n.s.). Participants commented that both Word and Phrase suggestions were often distracting, confirming the findings of a prior study [28].…”
Section: Subjective Measuressupporting
confidence: 79%
“…Despite its utility and near-ubiquity on mobile devices, word prediction has received relatively little research attention in mobile text entry. With appropriate parameter choices, a system can offer both corrections for mistakes and completions for partially entered words [5], but offering suggestions can incur costs of perception and interaction that hinder entry speed [28].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown asymmetries between objective performance and subjective experience of assistive user interfaces (Quinn and Cockburn, 2016;Quinn and Zhai, 2016), but not the influence of sequencing their successes and failures, as examined here.…”
Section: Stimuli For Sequencing Effectsmentioning
confidence: 41%
“…Snap-to-grid eliminates many uncontrolled variables that occur in other assistive domains. For example, if text-entry autocorrect were used, it would be difficult to control the timing and presence of user errors, potentially requiring artificial constraints on error-free performance that may influence the results (Quinn and Zhai, 2016).…”
Section: Stimulus For Momentary Experiencementioning
confidence: 99%